Testing the EKC Hypothesis Considering Trade Openness, Urbaniza-tion, and Financial Development in Indonesia - Moalla, Maya (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2024)
This paper delves into testing the validity of the Environment Kuznet's Curve (EKC) theory during the period spanning from 1970 to 2019, employing Narayan and Narayan's (2010) suggestion: if the long-term income elasticity is lower than the short-term one, the nation has effectively lowered its CO2 releases while observing an income surge, considering CO2 gas emissions as the environmental harm proxy; utilizing the Bounds Cointegration test. As far as we are aware, this marks the inaugural research for Indonesia scrutinizing the EKC's authenticity employing Narayan and Narayan's (2010) approach. The findings indicate that the EKC theory holds true in the interval studied because the long-term GDP elasticities doesn’t exceed the short-term ones.